(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2025)
Objective: To investigate the care, challenges, and difficulties faced by the surgical nursing team when caring for patients undergoing tracheostomy during the intraoperative and immediate postoperative periods. Method: A qualitative, descriptive study conducted through individual interviews with 14 members of the surgical nursing team in the second semester of 2023. The data were analyzed using content analysis. Results: The participants listed some of the nursing care provided to patients undergoing tracheostomy surgery, such as airway suctioning and changing the dressing and securing tie. There was also disagreement regarding the sequence of airway suctioning and dressing/tie changes. Regarding challenges and difficulties, the participants highlighted the need for health education for the tracheostomized patient, their family, and the professionals involved. Conclusion: The concepts and practices of the nursing team need to be updated due to gaps identified in their knowledge about care and guidance for the tracheostomized patient.